ANALISIS POTENSI MASYARAKAT “UMA LENGGE” DI DESA MARIA WAWO KABUPATEN BIMA SEBAGAI DESA WISATA (TOURISM VILLAGE) - Adi Hidayat Argubi; Ruli Inayah Ramadhoan; Tauhid Tauhid (Sadar Wisata: Jurnal Pariwisata, 2019)
AbstractThe purpose of this research is to find out the various potential attractions of the Uma Lengge tourist attraction Maria Wawo Village in Maria Village, Wawo Bima sub-district as a tourist village. This type of research used in this research is descriptive research. This research was conducted in Maria Village, Wawo Sub-district, Bima District. The stages of data collection are observation, structured interviews, questionnaires, and literature study. While the data analysis method used is descriptive qualitative, SWOT, and value scale analysis. The results showed that the potential of Wawo Tourism Village as one of the attractions in Bima Regency was physical potential that included "Uma Lengge" (Bima traditional house), typical rural natural scenery, Wawo village museums and Wawo Tourism Village recreation parks. Whereas its non-physical potential is Wawo culture, art, community activities in Wawo tourism village. Facilities that are available in Wawo Tourism Village are a resting place or shelter, parking area, toilets / toilets and worship facilities in the form of a small mosque. The final results of the perception of the public and tourists showed a positive support for the development of the Tourism Village Wawo as one of the cultural tourism objects in the Regency of Bima.